Taxes and Organizational Form: A Comparison of Corporations and Master Limited Partnerships - Guenther, David A. (The Accounting Review, 1992)
[Much of the research in positive accounting theory deals with whether managers choose accounting methods that reduce or minimize certain costs faced by firms, such as the cost of violating bond covenant restrictions, political costs, and the tax cost associated with the use of the FIFO rather than the LIFO inventory method. However, this research ignores some more fundamental costs associated with the legal form under which the firm chooses to operate, a much larger issue that precedes the choice of accounting methods. This article examines this larger issue by focusing on the trade-off that exists between tax costs and transaction costs in the choice of organizational form. Scholes and Wolfson (1986, 1989) assert that an organization's form is chosen to minimize both tax costs and transaction costs. Under this theory, if the corporate form has a greater tax cost than that of an alternative form, the partnership, the corporate form would not be chosen unless the transaction costs of the partnership form exceed those of the corporate form. Fama and Jensen (1983b, 327) examine costs of alternative organizational forms and state that "the form of organization that survives in an activity is the one that delivers the product demanded by customers at the lowest price while covering costs." Although Fama and Jensen specifically excluded tax costs from their analysis, Scholes and Wolfson argue that both relative tax costs and relative transaction costs are important determinants of organizational form choice, and that changes in relative tax costs will result in changes in form. They also make the following predictions about the effect of the 1986 Tax Reform Act: corporations will be replaced as an organizational form by partnerships for new ventures financed with equity; many existing corporations will convert to partnership form; absent this conversion, many corporations will add debt to their capital structure. These predictions lead directly to two questions. First, how do tax laws affect the choice of business entity? Second, what happens when these tax laws change? These two general questions are investigated here through two more specific research questions. The first is, What are the incremental tax costs and transaction costs of alternative organizational forms (corporations and master limited partnerships) available to large, publicly traded firms? The second is, How will managers of existing corporations respond to a tax law change (the 1981 Economic Recovery Tax Act) that causes the tax cost of the corporate form to increase relative to that of the partnership form? The results of empirical tests of four hypotheses developed to investigate these research questions indicate that, for the period 1978-85, the corporate form resulted in a significantly greater average tax cost than the partnership form, and this incremental tax cost increased significantly after the 1981 Economic Recovery Tax Act (ERTA). Partnerships are found to have a significantly lower return on assets and sales than a matched sample of corporations. Responses of managers to increasing tax costs of the corporate form after 1981 are predicted to be (1) increasing long-term debt, (2) increasing non-dividend distributions, and (3) decreasing dividend payout ratios. Empirical results for both univariate and multivariate tests are consistent with these predictions. These results make a significant contribution to accounting research for two reasons. First, they demonstrate a relationship between changes in relative tax costs of alternative (competing) organizational forms and changes in such fundamental elements of capital structure as debt levels, non-dividend distributions, and dividend payout ratios. Previous research on the relationship between taxes and capital structure (e.g., Bradley et al. 1984; DeAngelo and Masulis 1980; MacKie-Mason 1990; Titman and Wessles 1988) has not considered the effect of the tax cost of alternative organizational forms. Second, the results provide empirical support for predictions by Scholes and Wolfson (1986, 1989) and Petruzzi (1988) regarding responses of corporations to increases in relative tax costs (i.e., Scholes and Wolfson predict increasing long-term debt; Petruzzi predicts increasing non-dividend distributions).]